Hjalmar Schacht, Sang Diktator Perekonomian Jerman (Sebuah Tinjauan Historis) - Daniel Ramadhan; Wawan Darmawan; Achmad Iriyadi (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2017)
This article is the result of the research that discusses about the role of Hjalmar Schacht in building the German economy in 1933-1939. The main problem that is studied in this article is